Response of Spring Onion (Allium fistulosum L) on the Application of Bio-Stimulant Solution - Oñal, Jr., Paulino A; Arcillas, Kimberly F.; Elumba, Jula T.; Andrade, Francis E.; Cortez, Manuel D.; Baldonebro, Jessel Jane G. (Future Science / FSH-PH Publications, 2024)
Spring Onion (Allium fistulosum), is a perennial plant and a native of Eastern Asia. It is rich in vitamins A and K, iron, calcium, and dietary fiber, which contribute to various health benefits, blood pressure and cholesterol levels and improve blood regulation. The study aims to evaluate the response of spring onion to the different levels of concentration of bio-stimulant. Around 160 spring onion plants were utilized as planting materials. Before planting, extra leaves were cut to around 3 inches and roots were trimmed off too. The study was conducted at the School of Agriculture, University of Negros Occidental–Recoletos, Philippines using a Complete Randomized Design (CRD). All data gathered were statistically computed, and subjected to ANOVA using STAR 2.0.1. The experiment has four treatments: 0%, 20%, 30%, and 40% BSS, respectively, and was replicated four times. Results indicate that the application of 30% BSS significantly enhances the height to 32.02cm higher by 2.09cm for those with 0% BSS at 29.93 cm only, On the number of slips, 30% BSS has a greater number of slips of 3.42 against those with 0% BSS at 2.17 slips only. Biomass accumulation is highly significant with 3,375.00kg/ha for 30% BSS higher by 1,562.50kg/ha for 0% BSS. The total yield for 30% BSS is 3,000.00kg/ha significantly higher by 1,562.50kg/ha for 0% BSS with 1,437.50kg/ha only. Based on these findings, the application of a 30% BSS is recommended to optimize some of the agronomic attributes and yield of spring onions.